Re-analysis of Nigerian 2006 census age distribution using growth rate and mortality level (2014)
The usefulness of human population age structure in public health research is enormous, but age misreporting and an incomplete Vital Registration System (VRS) in Nigeria constitute a serious challenge. Age misreporting affects the true estimate of basic demographic parameters which are part of yardsticks for measuring the growth, development and well-being of a nation, thus the need to refine the age structure in Nigeria is important. This study was conceived with the view to refining the 2006 census age distribution using growth rate and mortality level. The Logit transformation system and Coale-Demeny life-table were used for data analyses. This study revealed that there was a gross age misstatement across all age categories, but age errors were more pronounced among females than males. The pattern of either under-reporting or over reporting of ages was similar for both sexes. Also, there was tendency to under-report ages 0 to 19 years and above 55 years, whereas gross over-reporting of age was observed in ages between 20 and 55 years. Good VRS and showing certificate of birth as evidence of age during census enumeration will reduce the errors in age reporting in future censuses in Nigeria.